Peningkatan Daya Saing: Pendekatan Paradigmatik-Politis - Riswandha Imawan (Jurnal Ilmu Sosial dan Ilmu Politik, 2002)
As liberal-based political-economic order increasingly globalised, each country have to geard in improving its competitiveness. Each country attempt to optimise its comparative advantage in order to survive in such an order. Judging from political perspective, the author argues that capability to perform competitively at the global and international arena, Indonesia has to institutionalise domestic political economis system, both at national and local level. The political format suggested for that purpose is resemble to what Deborah Stone calls: the polls model. It is true the globalised world order tend to marginalised the role of the government, yet, the government of Indonesia responsible to set up a sound policy for improving national and local competitiveness. Nonetheless the state role is to empower, rather than to dominate, let alone dependency creating. The challenges and strategy to meet them is offered at the end of this article.